Harnessing nanoparticle technology for precision medicine in head and neck cancer: Targeted delivery, immunomodulation, and clinical translation - Karthikeyan Elumalai; Sivaneswari Srinivasan (Nano TransMed)
Head and neck cancer (HNC) remains a significant challenge in oncology due to poor drug delivery and an immunosuppressive tumour microenvironment (TME). This review focuses on the role of nanoparticles (NPs) in addressing challenges in HNC treatment, highlighting their potential to enhance efficiency and targeting. Researchers are studying different kinds of NPs, like liposomal, polymeric, dendritic, and gold nanoparticles (AuNPs), to see how they can improve drug delivery and change the tumour environment. To improve treatment results, we use specific strategies like targeting receptors, releasing substances inside cells in a controlled way, and adjusting the immune response. The review talks about how NPs focus on cancer-related fibroblasts, stop new blood vessel growth, and tackle problems in moving these treatments into real-world use. These issues include safety, toxicity, being able to produce them on a large scale, and following regulations. Finally, emerging trends, such as hybrid NPs and personalized nanomedicine, are proposed. Nanoparticle technology can greatly change how we treat head and neck cancer. It can improve how drugs are delivered, alter the environment around tumours, and tailor treatments to individual patients, which can make life better for them. This could lead to a new approach in cancer care.in cancer treatment.